2023
DOI: 10.1177/03331024221139253
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetics and causal relationships between migraine and thyroid function traits

Abstract: Background Epidemiological studies have reported a comorbid relationship between migraine and thyroid dysfunction. Methods We investigated the genetic relationship between migraine and thyroid function traits using genome-wide association study (GWAS) data. Results We found a significant genetic correlation ( rg) with migraine for hypothyroidism ( rg = 0.0608), secondary hypothyroidism ( rg = 0.195), free thyroxine (fT4) ( rg = 0.0772), and hyperthyroidism ( rg = –0.1046), but not thyroid stimulating hormone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Furthermore, there may be a connection between migraine and various vascular diseases through factors like endothelial dysfunction, hypercoagulability, platelet aggregation, and the use of non-steroidal anti-inflammatory drugs ( Adelborg et al, 2018 ). At last, it has been suggested that the risk of VTE may be heightened due to immobilization during migraine attacks ( Adelborg et al, 2018 ; Tasnim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there may be a connection between migraine and various vascular diseases through factors like endothelial dysfunction, hypercoagulability, platelet aggregation, and the use of non-steroidal anti-inflammatory drugs ( Adelborg et al, 2018 ). At last, it has been suggested that the risk of VTE may be heightened due to immobilization during migraine attacks ( Adelborg et al, 2018 ; Tasnim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with practice in previous studies 30 , 31 , 46 , 92 94 , we assessed the validity of our IVW estimates using two additional models, namely, the MR‒Egger (which can produce valid estimates by correcting pleiotropy even with up to 100% invalid IVs) and the weighted median (which can produce valid estimates with up to 50% invalid IVs). We also tested the assumption of no horizontal pleiotropy using the MR‒Egger intercept.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a significant genetic correlation with mutual single nucleotide polymorphisms (SNP) and gene loci has been found between migraine and thyroid dysfunction, particularly in hypothyroidism. This suggests that their complex association might be due to shared molecular genetic mechanisms [ 6 ]. Additionally, the treatment of subclinical hypothyroidism was effective in reducing both the frequency and severity of migraine attacks [ 166 ], which is also confirmed by a recent randomized controlled trial [ 167 ].…”
Section: Thyroid Dysfunctionmentioning
confidence: 99%
“…Some studies have shown a possible role of the insulin receptor in the pathophysiology of migraine [ 5 ]. Furthermore, genetic and immune mechanisms may explain a bidirectional association between migraine and thyroid dysfunction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%